2020
DOI: 10.1371/journal.pone.0244749
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasonic-assisted extraction of polysaccharides and triterpenoids from the medicinal mushroom Ganoderma lucidum and evaluation of their in vitro antioxidant capacities

Abstract: Ganoderma lucidum (Fr.) Krast, commonly known as “Lingzhi” in Chinese, is a medicinal mushroom that is rich in biologically active substances. Polysaccharides and triterpenoids are the two major components responsible for the bioactivity of this fungus. In the present study, the ultrasonic-assisted co-extraction (UACE) of polysaccharides and triterpenoids from G. lucidum was optimized using response surface methodology with a desirability function, with the equal importance for the two components. Following si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
(20 reference statements)
1
17
1
Order By: Relevance
“…However, when compared with microwave-assisted extraction, ultrasound-assisted extraction is less robust, and the particle size is also a critical factor [ 27 ]. Zheng et al (2020) [ 28 ] showed that the triterpenoid yield increased as the extraction temperature changed from 40 °C to 80 °C and then decreased above 80 °C by microwave. The bitter melon extracts were heated at various temperatures, including 30, 60, and 100 °C, and the samples were collected at 5 min intervals for saponin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when compared with microwave-assisted extraction, ultrasound-assisted extraction is less robust, and the particle size is also a critical factor [ 27 ]. Zheng et al (2020) [ 28 ] showed that the triterpenoid yield increased as the extraction temperature changed from 40 °C to 80 °C and then decreased above 80 °C by microwave. The bitter melon extracts were heated at various temperatures, including 30, 60, and 100 °C, and the samples were collected at 5 min intervals for saponin.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction efficiency of microwave-assisted extraction is related to the mechanical effects of the rotation of molecules, which are due to a microwave-induced dipole, causing the migration of the ions, which can improve the penetration of the solvent into the matrix. This disrupts the cell wall, thereby releasing the intracellular products, permitting the dissolution of components that are to be extracted [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al isolated some triterpenoids. Two of them, Lingzhin E and Lingzhin F, exhibited antioxidant activity by the ABTS method Zheng et al (2020) used ethanol maceration to extract the triterpenoids and evaluated their antioxidant activity using the DPPH method, which depends on the concentration of terpenoids. Zhu et al (1999) mentioned that the fraction with terpenes consisted of ganoderic acids A, B, C, and D, lucidic acid B and ganodermanontriol as the main compounds, and were noted to have the strongest antioxidant effect.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Consequently, new extraction methods have emerged, in the last decades, including sonication, microwave-assisted extraction, ultrasound-assisted extraction, supercritical fluid extraction, fluidized-bed extraction, and pressurized-liquid extraction ( Saleh et al., 2020 ). A rapid, simple, and effective extraction method is the use of ultrasonic waves to produce cavitation in the solvent, increasing the penetration of solvent considerably into the plant material ( Zheng et al., 2020 ). Ultrasound-assisted extraction (UAE) compared to other extraction methods, is a green technology that provides a simplified manipulation, a high reproducibility in a shorter time, decrease in temperature, reduction in organic solvent intake, and high efficiency with lower energy consumption ( Fan et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%